Protein Precipitation by Metal Hydroxides as a Convenient and Alternative Sample Preparation Procedure for Bioanalysis - Emanuele Salina; Luca Regazzoni (Molecules)
Protein precipitation is widely used for sample preparation ahead of liquid chromatography. This step is required to analyze small molecules without the interference of proteins contained in the matrix. Organic solvents and acidic chemicals are the two most popular reagents used for this scope. Organic solvents are quite effective precipitating agents, but require a medium-to-large sample dilution. Moreover, a high concentration of organic solvents in sample media can affect reversed phase separations. Therefore, an evaporation step, followed by the resuspension of the analytes in appropriate media, is sometimes required. On the contrary, the addition of acidic compounds is more straightforward, since it keeps the supernatant aqueous and does not require evaporation, but the extreme pH can cause the degradation of analytes and the stationary phase. Herein, an alternative method for protein precipitation using the addition of zinc hydroxide was tested. The main advantages of this method over the other precipitating reagents are the minimal sample dilution required and the maintenance of aqueous media at nearly neutral pH which ensure analyte stability. The protocol ensured an effective protein removal before the analysis of small molecules in biological matrices, resulting in full compatibility with reversed phase chromatography coupled with both UV and mass spectrometric detectors.